Analysis of Constraints on the Implementation of the Independent Curriculum in PAUD Level Mobilizing Schools in Situbondo District - Fathor Rakhman; Miftahus Surur (South Sulawesi Education Development (SSED), 2024)
This study uses a qualitative research approach to discuss the obstacles to the implementation of the independent curriculum in PAUD-driving schools in Situbondo Regency. Qualitative research methods were used to collect data through in-depth interviews with PAUD teachers in kindergartens in Situbondo, including Nurul Anshor Islamic Kindergarten, DWP 1 Besuki Kindergarten, DWP 1 Asembagus Kindergarten, Kartika IV-71 Kindergarten, Nurul Huda Kindergarten, DWP 1 Jatibanteng Kindergarten, and Hasyim Asy'ari Kindergarten, direct observation in schools that were the object of research, and document analysis related to the implementation of the independent curriculum. The results of this study show obstacles. These obstacles include differences in students' learning styles and initial abilities, adaptation to the